2016
DOI: 10.1093/ofid/ofw171
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Aspergillosis Associated With Severe Influenza Infections

Abstract: Background. Invasive aspergillosis may occur in the setting of severe influenza infections due to viral-induced respiratory epithelium disruption and impaired immune effects, but data are limited.Methods. A retrospective study was conducted among severe influenza cases requiring medical intensive care unit (ICU) admission at an academic center during the 2015–2016 season. Data collected included respiratory cultures, medical conditions and immunosuppressants, laboratory and radiographic data, and outcomes. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
107
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 46 publications
6
107
3
Order By: Relevance
“…Two systematic reviews of invasive aspergillosis complicated by Influenza infection reported 68 and 57 total cases (Alshabani et al, 2015; Crum-Cianflone, 2016a). One review of immunocompetent and immunocompromised patients with Influenza and IPA reported Influenza A in 93% of cases, with the majority of these having H1N1.…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews of invasive aspergillosis complicated by Influenza infection reported 68 and 57 total cases (Alshabani et al, 2015; Crum-Cianflone, 2016a). One review of immunocompetent and immunocompromised patients with Influenza and IPA reported Influenza A in 93% of cases, with the majority of these having H1N1.…”
Section: Discussionmentioning
confidence: 99%
“…Also, invasive pulmonary aspergillosis (IPA) caused by the fungal Aspergillus fumigatus is recently recognized as a co-infection occurring in 20-25% of influenza patients who are admitted to the intensive care unit (ICU) [7,8]. Both bacterial as well as fungal pulmonary co-infections are associated with increased mortality rates [7,[9][10][11]. In addition, viral co-infections [12] and reactivation of viruses that reside latent in the host, such as Cytomegalovirus (CMV), Epstein barr virus (EBV) and Herpes simplex virus (HSV) are frequently encountered in influenza patients as well [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…CMV disease/viremia have consistently been identified as risk factors for invasive fungal infections in all transplant populations . More recently, viral disruption of the respiratory epithelium with impaired local immunity due to Influenza have been identified as specific risk factors for Invasive Aspergillosis in the general population …”
Section: Discussionmentioning
confidence: 99%